PERBANDINGAN TINGKAT KEPUASAN MASYARAKAT YANG MEMAKAI GIGI TIRUAN BUATAN DOKTER GIGI DAN TUKANG GIGI DI BANJARMASIN - Muhammad Arfah Akbar; Rosihan Adhani; Rahmad Arifin; Ika Kusuma Wardani; R. Harry Dharmawan Setyawardhana (Universitas Lambung Mangkurat, 2024)
Background: Riskesdas data for South Kalimantan Province for 2018 stated that 3.3% of the population who received denture installation treatment in the last 12 months in Banjarmasin, 22.9% of the population in Banjarmasin received treatment at dentists and 0.79% received treatment at dental artisans. There are differences in the manufacture of dentures made by dentists and dental artisans, both in terms of quality, indications, contraindications, and cost. Purpose: To analyze the comparison of the level of satisfaction of people who use dentures made by dentists and dentists in Banjarmasin. Method: Using a comparative analytical method with a cross-sectional approach. The sampling technique uses quota sampling. The population is Dentist and Dentist patients in Banjarmasin City. The minimum sample size is calculated using the Lemeshow formula and the results are 100 samples. Results:. Analysis of the Mann Whitney test data yielded a significant value of 0.000 <0.05 which indicated that the H0 decision was rejected or meant that there was a difference in satisfaction with dentures made by dentists and dental artisans. Conclusion: There is a difference in satisfaction with dentures made by dentists and dentists, where the satisfaction level of users of dentures made by dentists is higher than the level of satisfaction made by dentures made by dentists in Banjarmasin City.Keywords: Artisan Dental, , Dentist, Denture, Satisfaction.